Efforts to Handle Cases of Minors in Driving Motor Vehicles (Case Studies on Police and Lease Islands) - Jamila Wakano; Fatimah Sialana; Aisa Abas (CV. Rayyan Dwi Bharata, 2022)
This research is a qualitative descriptive qualitative research that aims to find outvhow to handle cases of minors in driving a motorized vehicle. This research was carried out at the Ambon Island police station and the Lease Islands in Maluku Provinsi.data were collected by interviewing the traffic Police and minors. The results of this study indicate that the factors that cause the use of motorized vehicles by children in the Polresta area.and Lease Islands are factors of ignorance, personal urges, family urges, social urges, not deterrence and opinions are not obliged too order traffic.